2016
DOI: 10.3390/nu8110702
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Composition in the Two Years after Initiation of Haemodialysis: A Retrospective Cohort Study

Abstract: Malnutrition is common in haemodialysis (HD) and is linked to poor outcomes. This study aimed to describe changes in body composition after the initiation of HD and investigate whether any routinely collected parameters were associated with these changes. The study cohort came from the HD population of a single centre between 2009 and 2014. Body composition measurements were obtained from a database of bioimpedance results using the Body Composition Monitor (BCM), while demographics and laboratory values came … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
13
0
2
Order By: Relevance
“…These changes coincided with a mean increase in BMI of 0.6 kg/m 2 . These data were later confirmed by a study from Keane et al, who observed a mean increase in FM of 0.7 kg and a decline in LTM of 0.9 kg over a 2‐year period following the start of dialysis . In a cohort of 824 PD patients, LTI declined by a mean of 1.1 kg/m 2 whereas FTI increased by 1.9 kg/ m 2 , with a significant inverse relationship between changes in both body compartments.…”
Section: Prevalence Of Abnormalities In Body Composition In Dialysis supporting
confidence: 53%
See 1 more Smart Citation
“…These changes coincided with a mean increase in BMI of 0.6 kg/m 2 . These data were later confirmed by a study from Keane et al, who observed a mean increase in FM of 0.7 kg and a decline in LTM of 0.9 kg over a 2‐year period following the start of dialysis . In a cohort of 824 PD patients, LTI declined by a mean of 1.1 kg/m 2 whereas FTI increased by 1.9 kg/ m 2 , with a significant inverse relationship between changes in both body compartments.…”
Section: Prevalence Of Abnormalities In Body Composition In Dialysis supporting
confidence: 53%
“…The 3C model recognizes the presence of ECF and ICF in adipose tissue and calculates the so‐called OH compartment based on the assumption of normal hydration ratios for lean and adipose tissue, respectively . Thus, the 3C model expresses three body compartments: LTM, ATM, and the OH compartment as an indicator of FO (Figure ), which can also be negative and in this case points to fluid depletion . Lipid containing FM can be derived from ATM by taking into account the hydration state of adipose tissue .…”
Section: Short Technological Background Of the 3c Bis Modelmentioning
confidence: 99%
“…In HD patients it is well established that lean tissue loss is independently associated with poor outcomes [16,21], but the effect of changes in fat mass is more complicated. Attempts to verify the potential survival benefit of increased fat mass have shown mixed result [22][23][24][25][26]. The advantage of avoiding IDH occurrence by a high LTI remained significant, even after multivariable adjustment including C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
“…Current international recommendations for daily dietary protein intake are 0.8 g/kg for the general population [40] [46,47]. Insu cient protein intake in ESRD patients may lead to di culty counteracting protein loss and catabolism during dialysis [48]. A high protein diet, similar to the Western diet (which is rich in animal proteins and fats), stimulates the overgrowth of proteolytic bacteria, resulting in dysbiosis and accumulation of proteolytic-derived uremic toxins [49].…”
Section: Discussionmentioning
confidence: 99%